en - Ulfah Nurjannah Nasution; Mayasari Mayasari (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2023)
Mangupa text can be regarded as a cultural text because the text is a text or written material that reflects a way of life that is owned by a group of people. This research is qualitative research and the method is document (text) analysis, data analysis uses translation theory by Newmark. This theory divides translation into eight methods: Word for Word Translation, Literal Translation, Free Translation, Adaptation Translation, Idiomatic Translation, Faithful Translation, Semantic Translation, and Communicative Translation. The findings of the research showed 23 text in a Mangupa Text from Mandailing Language Into Indonesian that is exactly divisible for by the use of Newmark’s theory that the translation method which is the most frequently used by the translator is semantic translation and word for word translation.